Non-Compulsory Settlement of Disputes in 1982 UNCLOS and the Jurisdictional Conundrum - Vyas, Prakhar (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The following essay is written regarding the provision of Noncompulsory settlement of disputes provided in Article 298 of the United Nations Convention on Law of the Sea which allows the parties to make the prior declaration regarding the exclusion of certain issues from the jurisdiction of the convention and thereby from the institutions provided for in the convention for the redressal of those disputes. The essay is divided into five parts namely the Introduction, Issues, Analysis, Suggestions and the Conclusion. Through Introduction it gives the brief overview of the provision and the convention, through Issues it highlights the various problems which have arisen as a result of the provision including the instances where the countries used it against the very purpose for which it was drafted. The Analysis section includes the study of various reasons as to why the countries are choosing to adopt Article 298 even though it acts as a weapon firing both the ways. The last two parts are the suggestions and the conclusion where the essay covers the steps which should be taken into consideration in order to solve the issues thereby keeping in mind the objective of the drafters of providing flexibility to the countries. The essay derives its sources from the various books as well as research papers written by reputed authors.
Keywords: Non Compulsory Settlement of Disputes; Article 298; United Nations Convention on Law of the Sea; Issues, Analysis; Suggestions